The relationship between transformational leadership behavior and organizational commitment among teachers in the district of Padawan, Kuching / David Anak Rangot - Rangot, David (2013)
The aim of the research is to determine the relationship between head teacher transformational leadership behaviors and teacher organizational commitment in primary schools based on teachers' perspectives. The purpose of the research is also to identify the head teacher transformational leadership based on five dimensions, and to determine whether there are significant relationship in the level of teachers school commitment based on three components with respect to the selected background variables of gender, years of teaching experiences and school location. The study also sought to identify the kind of transformational leadership behaviors foster teachers school commitment. A quantitative research employing a survey method was conducted using questionnaire as a research instrument. The research involved 239 teachers selected based on non-random sampling method. The data collected were analyzed using descriptive and inferential statistics. The result showed that there was no significant relationship between level of head teachers' transformational leaderships and teacher organizational commitment but there were some weak links between transformational leadership variables with organizational commitment variables i.e., affective commitment recorded significant relationship with 'Models Behavior* and 'Providing Intellectual Stimulation'. The lowest score recorded in 'Models Behavior' implies that head teachers might probably lack exposure to be exemplary leaders. Therefore, courses on leadership should be conducted for them on a yearly basis.